(untitled) - Elster, Jon (Cambridge, 1983)
Technical change, defined as the manufacture and modification of tools, is generally thought to have played an important role in the evolution of intelligent life on earth, comparable to that of language. In this volume, first published in 1983, Jon Elster approaches the study of technical change from an epistemological perspective. He first sets out the main methods of scientific explanation and then applies those methods to some of the central theories of technical change. In particular, Elster considers neoclassical, evolutionary, and Marxist theories, whilst also devoting a chapter to Joseph Schumpeter's influential theory.
Keywords: Đổi mới công nghệ,Technological innovations; Khía cạnh xã hội,Social aspects